Pembangunan Mini Garden Sebagai Pembuka Potensi Wisata Desa Sambirejo Kabupaten Jombang - Wafiq Ainnur Rozzan; Putri Intana Ramadhani; Musdlolif Fadlun Huda Maramida; Dhian Satria Yudha Kartika (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
This research is entitled "Development of a Mini Garden as an Opener for the Tourism Potential of Sambirejo Village, Jombang Regency". With the aim of knowing the Mini Garden development process to open up the natural tourism potential of Sambirejo Village with the unavailability of tours that can be visited by the general public. Potential is something that must be considered further, it is intended that all the advantages and potential that can be developed can be maximized perfectly. Of course everything is inseparable from the role of the parties concerned, either directly or indirectly. This development is expected to be a form of accelerating village development to encourage community welfare. The method used in this study is a qualitative research method with more emphasis on the analysis of a condition through ways of thinking, data collection techniques through observation and documentation. From the results of the study it can be concluded that the construction of a mini garden provides new innovations for Sambirejo Village, especially in terms of tourism potential which is later expected to provide real benefits for the village community.